Peran Kepemimpinan Pendidikan dalam Manajemen Inovasi Pembelajaran - Puspito Rini, Puput (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
Educational leadership is a field of fundamental study at the intersection of leadership, management, and pedagogical theories that includes the systematic efforts of leaders in directing educational institutions towards quality, innovative, and impactful goals. This study aims to examine the role of educational leadership in learning innovation management through four dimensions, namely the influence of leadership style on innovation culture, the contribution of transformational-pedagogical dimensions, the effectiveness of institutional operational management, and the formulation of comprehensive and applicable innovative leadership models. The method used is Systematic